Optimization of fat yield from rambutan (Nephelium lappaceum L.) seed under convective drying - Ahmad, So'bah; Anuar, Mohd Shamsul; Taip, Farah Saleena; Shamsudin, Rosnah (Universiti Kuala Lumpur Publishing, 2016)
The optimization of the process variable; temperature and drying time, under convective drying in an automatic electric oven were studied for the rambutan clone R4 seed fat yield. The optimization conducted using response surface methodology central composite design of experiment. The result indicated both process variables have positive effect upon fat yield within studied range. However, drying time exhibited a higher positive effect in increasing the fat yield. The optimum drying condition was obtained at 54.02 °C for 36.52 h drying time yielding 38.65% fat yield. The response surface methodology used in this study was able to predict the optimum drying condition for fat yield of rambutan seed clone R4 via linear and square mathematical model with higher adjusted coefficient determination (